Respiratory syncytial virus immunisation overview. (22nd October 2020) - Foley, David A; Phuong, Linny K; Englund, Janet A
Abstract : Respiratory syncytial virus (RSV) continues to be a significant source of morbidity and mortality in both adults and children. Natural infection confers incomplete protection, permitting recurrent episodes. Treatment remains limited to supportive care. Initial endeavours to develop a vaccine resulted in an unexpected enhancement of RSV disease and increased recipient mortality. Current proposed strategies to prevent RSV infection rely on the principles of active and passive immunisation and utilise the highly conserved RSV F‐protein. Maternal vaccines administered in pregnancy may provide protection; trials are ongoing. Palivizumab, a monoclonal antibody, has a moderate preventative efficacy. A similar newer longer lasting formulation appears promising. A number of other novel options are being developed and are undergoing assessment. Progress has been made, with more vaccine candidates under consideration. We are edging closer to an effective solution to prevent RSV infection. If successful, the impact on paediatric morbidity, mortality, workload and cost will be substantial.